Compensation Issue in Clinical Trials Recent Indian Scenario - Yadav, Mukesh; Thakur, Pramendra Singh; Rastogi , Pooja (Journal of Indian Academy of Forensic Medicine, 2014)
Hon’ble Supreme Court has shown its concern for protection of human rights of those who were the research participants for clinical trials and suffered either death or serious adverse events. These research participants had not given adequate compensation or no compensation at all. A Public Interest Litigation (PIL) has been filed in the Supreme Court of India in the year 2012 by a NGO, consequently a committee has been constituted by the Ministry of Health and family Welfare, government of India to look into the matter of compensation. Recently a formula to determine the quantum of compensation in the cases of clinical trial related Serious Adverse Events (SAEs) including deaths occurring during clinical trials have been evolved by a committee formed under the Drugs and Cosmetics Rules. This research paper deals with critical issue of compensation in clinical trial related SEAs including deaths of the research participants and initiative taken by the concern authorities including the directions given by the Supreme Court of India from time to time and provisions in the Drugs and Cosmetics (Amendment) Bill, 2013.